Studies on the Structural, Optical, Photocatalytic and Luminescence Properties of Monodispersed CdS Nanoparticles Capped with Moringa oleifera L. Leaf Extract - Goud, B. Srinivasa; Suresh, Y.; Odelu, G.; Annapurna, S.; Bhikshamaiah, G.; Singh, A.K. (Asian Journal of Chemistry, 2026)
This study reports the structural, optical, photocatalytic and luminescence properties of monodispersed cadmium sulphide nanoparticles (CdS NPs) synthesised via an eco-friendly green synthesis approach using Moringa oleifera leaf extract as a natural stabilizing and capping agent. Cadmium nitrate, cadmium sulphate and cadmium chloride are used as cadmium precursors, while sodium sulphide served as the sulphur source. X-ray diffraction (XRD) analysis confirmed the formation of cubic-phase CdS NPs with high crystalline nature. The optical properties are evaluated through UV-Vis absorption spectroscopy, revealing a band gap energy range of 3.08 to 4.92 eV. FTIR confirmed the presence of functional groups responsible for stabilisation of CdS NPs. The morphological characteristics, elemental composition and purity are assessed using FESEM and EDS. Small-angle X-ray scattering (SAXS) and transmission electron microscopy (TEM) determined the nanoparticle size to be below 5 nm, confirming their nanoscale dimensions. Photoluminescence (PL) spectra indicate strong emission properties, enhancing their potential use in optoelectronic applications. The photocatalytic activity of CdS NPs is evaluated by degrading methylene blue (MB) and rhodamine B (RhB) dyes under visible light irradiation, demonstrating their efficiency in environmental remediation and wastewater treatment. The results highlight the superior optical, structural and catalytic performance of M. oleifera-capped CdS NPs, making them promising candidates for advanced nanomaterial applications in solar cells, photocatalysis and biomedical fields.